A nonadride derivative from the marine-derived fungus Aspergillus chevalieri PSU-AMF79 - Baiq Nila Sari Ningsih (2022)
One new nonadride enantiomer, ent-epiheveadride, along with five known dioxopiperazine derivatives were isolated from the marine-derived fungus Aspergillus chevalieri PSU-AMF79. Their structures were identified by extensive spectroscopic analysis. The absolute configuration of ent-epiheveadride was determined by comparison of the specific rotation and electronic circular dichroism data with those of related known compounds. It exhibited antifungal activity against Cryptococcus neoformans ATCC90113 flucytosine–resistant and Candida albicans NCPF3153 with the MIC values of 128 and 200 µg/mL, respectively. In addition, the known L-alanyl-L-tryptophan anhydride displayed TMEM16A inhibitory activity with 65.0% inhibition at a concentration of 5 µg/mL.